Gerontological perspectives of Big Data analysis of mobile-based health data - Imre, Töviskes; Balázs, Molnár (Magyar Gerontológia, 2023)
The mass proliferation of smartphones with the features of general purpose computers is a major challenge for the iPhone in 2007. Medical use of these devices started in 2009 and today there are around 350,000 health apps in the world, are available, with hundreds of hundreds of millions of them, and they have more than 10 million users. Studies show that users are becoming more open to health apps and related mobile phone peripherals, use of assets (e.g. activity trackers).